Prospek Buah Srikaya sebagai Komoditas Unggulan di Kabupaten Sumenep: Prospect of Srikaya Fruit as a Superior Community in Sumenep Regency - Hidayat, Syarif Imam; Dewi, Shendy Maudina; Parsudi, Setyo (Jurnal Ilmiah Manajemen Agribisnis, 2024)
Srikaya fruit is one of the tropical fruits that is developed in order to increase fruit production. In Sumenep Regency, srikaya fruit is widely cultivated, but in general it has not been developed well even though there are quite a lot of enthusiasts. This study aims to analyze the prospects and commodities of srikaya fruit as a superior commodity in Sumenep Regency. The research location was chosen intentionally (purposively) in 3 sub-districts in Sumenep Regency, namely Saronggi District, Talango District, and Kota Sumenep District which are areas producing srikaya fruit. The types of data used are primary data and secondary data. The data analysis method in this study is qualitative descriptive analysis and Location Quotient (LQ) analysis. The prospects are studied using primary data through in-depth interviews with informants using purposive and snowball techniques, while superior commodities are studied using LQ analysis. The results of the study indicate that srikaya fruit in Sumenep Regency has quite promising prospects because the potential of natural resources is very supportive and there is a potential market with a lot of demand from within and outside the region. Based on the LQ analysis, for five consecutive years the LQ value of soursop fruit has always been more than 1. This means that soursop fruit is classified as a superior commodity where its production is not only able to meet its own needs but can also be distributed to other areas outside Sumenep Regency.